Efficiency of Assistant Robots in Cochlear Implant Surgery: A Systematic Review - Alireza Golchin-Namdari; Somayeh Falahzadeh; Adel Gholaminezhad (Vesnu Publications, 2017)
Introduction: Cochlear implant (CI) surgery is an invasive procedure in order to create hearing sense. This procedure may cause some risks such as cochlear damage. Therefore, it is needed to reduce these risks as much as possible. Future CIs will address three general goals: 1) reducing cochlear damage during surgical insertion, 2) more efficient operation that reduces the load of electrical stimulation required to produce appropriate loudness, and 3) deeper insertion into the scala tympany (ST) cavity in order to access cochlear neurons related to lower frequencies. In order to achieve these goals, we need high degree of precision to which the use of an assistant robot in surgery might be a good solution. The aim of this study was to assess the efficiency of the robotic systems in the cochlear implant surgery. Materials and Methods: Published research was identified by reviewing the scientific databases (Pubmed, ScienceDirect and Google Scholar) from 1980 to 2017 using relevant keywords. The researches were selected based on the input and output criteria. Results: This study focused on three robotic systems. One of the robotic systems acts as a magnetic guide. This system uses a magnetically tipped CI to insert into the cochlea and also rotating manipulator magnet as a magnetic guide that is located near the patient's head. The other robotic system determines the changes of the insertion angle of the electrode array into the cochlea by controlled electrode arrays insertion. The last robotic system reduces the invasiveness of the surgery by removing the need for mastoidectomy, replacing this with a direct tunnel approach known as direct cochlear access. Conclusion: These systems reduce the energy needed for the insertion of the electrode array, enable a deeper insertion into the cochlea in order to have an improved performance in CI, and reduce intracochlear damage during surgery. Therefore, both speech understanding in noise and sound quality will improve.